2019
DOI: 10.21003/ea.v180-15
|View full text |Cite
|
Sign up to set email alerts
|

Digital transformation of modern quality management

Abstract: Introduction. The need to transform modern management systems under the influence of total digitalization is an important and serious social goal of science and business. One of the key areas of management today is quality management. In this regard, the purpose of the paper is defining the specifics and main trends and risks of digital quality management transformation on the whole, as well as evaluating the development of modern quality management in the context of digitalization. Results. Based on the proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…What impact the digital transformation has on quality management practices, what changes there are for quality management and quality management professionals, what concepts of quality management may evolve in the future under this change -all these questions emerge and not all of them have an answer yet. Some propositions exist already that the digitalisation may become in the future one of the quality management keystones along with innovation, adaptability and resilience (Mayakova, 2019).…”
Section: Rtu 62nd International Scientific Conference On Economics An...mentioning
confidence: 99%
See 4 more Smart Citations
“…What impact the digital transformation has on quality management practices, what changes there are for quality management and quality management professionals, what concepts of quality management may evolve in the future under this change -all these questions emerge and not all of them have an answer yet. Some propositions exist already that the digitalisation may become in the future one of the quality management keystones along with innovation, adaptability and resilience (Mayakova, 2019).…”
Section: Rtu 62nd International Scientific Conference On Economics An...mentioning
confidence: 99%
“…Ivančić (Ivančić et al, 2019) has identified the following digital transformation dimensions: Strategy, People, Organisation, Customer, Ecosystem, Technology, and Innovation. The benefits, disadvantages and risks connected to the integration of digital technologies (Mayakova, 2019;Ralea et al, 2019), challenges of the implementation (Kovrigin & Vasiliev, 2020;Sjödin et al, 2018) and key lessons learned (Tabrizi et al, 2019) are also discussed in the scientific literature. Some studies focus on human aspects of digitalisation (Elg et al, 2020;Dengler & Tisch, 2020) and another research has been done on trends and tendencies of digital transformation (Lola & Bakeev, 2020).…”
Section: Digital Transformationmentioning
confidence: 99%
See 3 more Smart Citations